2018
DOI: 10.1159/000491494
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Squamous Cell Carcinoma Antigen Level and Tumor Volume in Head and Neck Cancer

Abstract: Purpose of Study: An association of squamous cell carcinoma antigen (SCC-Ag) level with cancer prognosis has been reported in many studies. Our investigators conducted the first study determining a correlation between the SCC-Ag level and the tumor volume in head and neck cancer. Procedures: The SCC-Ag level of patients were measured from the serum, whilst the tumor volume was calculated by the ellipsoid formula and verified by logistic software on radiology. The correlation between SCC-Ag level and tumor volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In this study, we observed that the SCC-Ag level adjusted for tumor staging was an independent prognostic factor for patients with ESCC, similar to the results of Shimada et al [15,25]. The most likely explanation was that the SCC-Ag level is mainly determined by tumor volume and internal potential for malignancy, such as expression of gene Wnt-11 [11,26], Fig. 4 Cancer-specific survival curve for the whole cohort of patients with ESCC according to the groups (Group A included low SCC-Ag and high albumin levels; Group B included patients with high SCC-Ag or low albumin levels; Group C included patients with low albumin and high SCC-Ag levels) Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we observed that the SCC-Ag level adjusted for tumor staging was an independent prognostic factor for patients with ESCC, similar to the results of Shimada et al [15,25]. The most likely explanation was that the SCC-Ag level is mainly determined by tumor volume and internal potential for malignancy, such as expression of gene Wnt-11 [11,26], Fig. 4 Cancer-specific survival curve for the whole cohort of patients with ESCC according to the groups (Group A included low SCC-Ag and high albumin levels; Group B included patients with high SCC-Ag or low albumin levels; Group C included patients with low albumin and high SCC-Ag levels) Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies suggested that serum squamous cell carcinoma antigen (SCC-Ag) levels had likely an effect on prognosis of malignant tumor [6][7][8][9], such as oral squamous cell carcinoma [7,10] and head and neck cancer [11,12]. Indeed, SCC-Ag is a widely used tumor marker in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…The search for noninvasive tumor markers in cancer is a rapidly growing area of research (Chen et al, 2008). SCC-Ag is an existing molecular biomarker that is used for clinical cancer diagnoses in China, but it is not a tumor-specific biomarker ( Jantharapattana et al, 2018). Aberrations in miRNA expression levels might be linked to the onset and progression of various types of cancer (Ferlay et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that serum SCC-Ag was at a significant risk level for the cancers in the hypopharynx, oral cavity and larynx [8,9]. In addition, there was a correlation between SCC-Ag level and the tumour volume in head and neck cancer patients [10]. It is wise to quantify the level of SCC-Ag to identify the condition of head and neck cancer, in order to provide the earlier treatment.…”
Section: Introductionmentioning
confidence: 99%